Peran Pembiayaan dalam Meningkatkan Kualitas Layanan Pendidikan - Aprilliantoni; Lailatul Fitriah Eka Putri; Rosulinawati (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to analyze access to education services on budget management, and its impact on service quality. The research method uses a qualitative approach with a case study method. This approach was chosen to gain an in-depth understanding of how education financing is implemented and managed in one of the public elementary schools in Bekasi. The results of the study indicate that schools face challenges of delays and limited funds, which have a negative impact on facilities, teaching materials, and extracurricular activities. Lack of transparency is also a problem that reduces stakeholder trust. However, with infrastructure improvements, optimal use of technology, and diversification of funding sources, schools can significantly improve access and quality of education. This study provides recommendations for improving the education financing system and services in schools, so that they can create a more inclusive learning environment and support optimal student development.